The influence of professional identity on how the receiver receives and responds to a speaking up message: a cross-sectional study - Melanie Barlow; Bernadette Watson; Elizabeth Jones; Fiona Maccallum; Kate J. Morse (BMC, 2023)
Abstract Background Research focused on understanding what enables or hinders health professionals to speak up about a safety concern has been to date predominately atheoretical and speaker focused. However, the role the receiver of the message plays in these often-difficult encounters is highly influential. To date, speaking up programs have created conversational mnemonics that technically should respectfully engage the receiver, yet speaking up remains challenging. This paper utilises Communication Accommodation Theory to explore the impact the communication behaviour and speaker characteristics has on the receiver of a speaking up message, and if these impacts differ between receiver groups (clinical disciplines). Method Clinicians (N = 208) from varying disciplines responded to two hypothetical speaking up vignettes, where participants were the receivers of speaking up messages. Analysis of variance was used to explore any potential differences between receiver groups. Results Findings indicated that the level of perceived accommodation and group membership, whether defined by speaker discipline or seniority, collectively influenced how the receiver of a speaking up message evaluated the interaction, which influenced their anticipated response to the speaker. Conclusions The receiver's perceptions and evaluations of the message, their own professional identity and the presence of others, influenced receivers' anticipated responses. This has direct implications on healthcare speaking up training and provision of care, as the varying clinical disciplines received and responded to the same messages differently.